Effect of Problem Based Learning Model on the Chemical Reaction Rate toward Critical Thinking Ability of Students - Kasmiati Kasmiati; Tahril Tahril; Vanny M. A. Tiwow (Jurnal Akademika Kimia, 2020)
This study aimed to identify the effect of the problem-based learning model on the reaction rate toward critical thinking abilities of students of MAN 1 Palu. This study was a quasi-experiment with a pretest-posttest control group design. Sampling was taken by purposive sampling technique with the sample of class XI MIA 3 as the experimental group (n = 18) and class XI MIA 4 as the control group (n = 14). The results of the study and data analysis obtained an average value of students' critical thinking skills from the questionnaire that the experimental group was 82.95%, higher than the control group (73.43%). The average value of students' critical thinking skills from the description test showed that the experimental group was 79.42%, higher than the control group (58.02%). Students' critical thinking skills data using parametric statistical analysis with t-test (right-party t-test) obtained tcount > ttable was 6.83 > 2.04 which corresponds to the H1 acceptance area, therefore H1 was accepted and H0 rejected. This means that students 'critical thinking skills in the experimental group were higher than in the control group. The results of this study concluded that the problem-based learning model had a significant influence on the thinking ability of students in grade XI on the reaction rate at MAN 1 Palu.